Floristic diversity and structure of the cloud forest of the Río Numbala, Zamora-Chinchipe, Ecuador: The “giant forest” of Podocarpaceae adjacent to the Podocarpus National Park - Yaguana, Celso (2012)
A forest inventory in a one-hectare permanent plot was conducted in the Numbala Reserve, a protected area of 1013 hectares, located in Palanda canton, Zamora- Chinchipe province, Ecuador, bordering the Podocarpus National Park, at 2100 m, 4°24’19”S, 79°03’36”W. The site is owned and administered by Nature and Culture International, a non-governmental conservation organization. All trees with DBH (diameter at breast height) ! 5 cm were inventoried in the plot. A total of 1091 trees and 171 species were recorded, with a basal area of 47.73 m"/ha and a total timber volume of 652 m3/ha. The dominant species of the forest by their diameters and heights are gymnosperms, two species of Podocarpaceae: Retrophyllum rospigliosii and Prumnopitys harmsiana, which together constitute 59.7% of the basal area and 79.6% of the total wood volume inventoried in the plot. A total of 35 trees of these two species have diameters greater than 70 cm and up to 47 m in height in the plot. Despite the dominance of the two species of gymnosperms, the floristic diversity is relatively high with 171 species of trees recorded in the plot, including numerous species of Rubiaceae, Lauraceae, Meliaceae, Myrtaceae and Melastomataceae. The values of basal area and timber volume, and the number of large trees greater than 70 cm DBH, are very high compared to other neotropical forests. There is bibliographic evidence from past decades of large stands dominated by Podocarpaceae, particularly Retrophyllum rospigliosii, in other Andean countries, but almost all have been cleared for timber extraction, and the Numbala forest is one of the last remnants of these "giant forests" of Podocarpaceae in the tropical Andes.